IMPACT OF GLOBAL MARKETS ON SAUDI STOCK MARKET - Saja Sami Saeed; Shabir Hakim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Globalization has led to interaction between people, businesses and governments of all countries, it will be a leader on international trade and investment also, derive help from the technology that provides them with information and influence in culture and economic development. It has also affected stock markets around the global. This study aims at investigating the impact of global market on Saudi stock market. In this regard, regression is used to analyze 10-years monthly data from Jan 2005 to Dec 2014 on Saudi stock market and global market. In addition, the relationship is tested for the impact of financial crisis. The test results reveal that global market has significant impact on Saudi stock market over ten- year period and in post-crisis period. The impact is not seen in the before-crisis period.